Impact of external heat transfer on the performance of a cold compressor used in superfluid helium system. (September 2020) - Dong, Xinbo; Wu, Jihao; Li, Junjie; Xu, Xiangdong; Su, He; Shang, Jin; Li, Qing; Gong, Linghui
Highlights: A numerical and experimental study has been made for a cold compressor. A platform is built to test cold compressor and then the CFD model is verified. The performance of cold compressor is affected by total external heat transfer. The mass leakage of tip clearance is intensified with external heat transfer. Abstract: Cold compressors are the core components needed for the development of a facility for large-capacity refrigeration at superfluid helium temperature. The compressor impeller operates at extremely low temperature and low pressure which involves a performance penalty due to heat transfer from the warm side of the machine to the cold side and thus affects the recycle of the cold exergy downstream. To investigate the heat transfer effect on cold compressor performance, a conjugate heat transfer analysis is performed with commercial CFD solver and is then validated with the experimental data tested at different rotation speed. Then a series of configurations of different thermal boundaries are analyzed to investigate the influence of heat transfer on performance. The simulated results show that the external heat transfer has a negative impact on pressure distribution. The helium gas inside the impeller flow domain is more sensitive to external heat leakage comparing with that inside the diffuser flow. More than that, the mass flow leakage through blade tip clearance is highly affected by the external heat transfer, which counts for the performance degradation.